Levels of some heavy metals in fishes From Pahang river estuary, Pahang, Malaysia - Yunus, Kamaruzzaman; Ong, Meng Chuan; Zabri, Rina Sharlinda; Bidai, Joseph (Asian Network for Scientific Information, 2010)
In this study, the concentration of Pb, Cu and Zn were determined in muscle, gills and stomach of six fish species caught from Pahang river estuary. These metals concentration were measured by ICP-MS in order to assess the fish contamination with these metals. This study showed that all catfishes (Arius sp.) presented the highest metals content. Tissue analysis revealed that the stomach accumulated the highest level of these metals. Based on the results, metal concentration in the edible part of the examined fish (muscle) were in the safety permissible levels for human consumption.